Inside Back Cover: Well‐Defined Single‐Site Monohydride Silica‐Supported Zirconium from Azazirconacyclopropane (Chem. Eur. J. 11/2015). Issue 11 (9th March 2015) - Hamzaoui, Bilel; Eter, Mohamad El; Abou‐hamad, Edy; Chen, Yin; Pelletier, Jérémie D. A.; Basset, Jean‐Marie
<x xml:space="preserve">Abstract</x> Monohydride silica‐supported zirconium The silica‐supported azazirconacyclopropane SiOZr(HNMe2)(η2‐NMeCH2)(NMe2) (1) leads exclusively under hydrogenolysis conditions (H2, 150 °C) to the single‐site monopodal monohydride silica‐supported zirconium species SiOZr(HNMe2)(NMe2)2H (2). Reactivity studies by allowing compound 2 to come into contact with ethylene, hydrogen/ethylene, propene, or hydrogen/propene, at a temperature of 200 °C revealed alkene hydrogenation. For more details, see the Full Paper by Jean‐Marie Basset et al. on page 4294 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>